Desempenho do aparato fotossintético em função das citocininas empregadas durante a fase de multiplicação in vitro de Aechmea blanchetiana (Bromeliaceae) - Rosa, Waldesse Storch (2017)
Tissue culture can contribute to the spread of several plant species of ecological or endangered importance, such as bromeliads. During the in vitro multiplication phase the use of cytokinins may be indispensable for the induction of lateral shoots in several species. However, analyzes on the physiological disorders induced by the growth regulators are still not well understood, especially on the photosynthetic apparatus. Thus, our objective was to evaluate the influence of cytokinins as a function of concentration, the multiplication rate, the performance of the photosynthetic apparatus and the stomatal functionality of Aechmea blanchetiana during the in vitro multiplication phase. Plants of A. blanchetiana previously established in vitro were inoculated in MS medium supplemented with 6-benzylaminopurine (BAP) or 6-furfurylaminopurine (KIN) at concentrations: 0, 5, 10, 15 or 20 μM. After 60 days of exposure to the growth regulators, the multiplication rate, the performance of the photosynthetic apparatus (Handy PEA fluorometer) and the characterization of the stomatal functionality of the explants as a function of the treatments were verified. No sprout formation was observed in the absence of exogenous cytokinins (control). The use of KIN did not induce shoot formation or increase of fresh mass, regardless of the concentration used. A significant increase of fresh mass and shoots was observed in plants cultivated with BAP, as the concentration increased. The type and concentration of cytokinins also influenced the photosynthetic apparatus of the seedlings at 60 days of culture in vitro. The transient fluorescence presented a typical form of OJIP curves with well-defined points J and I. The reduction in quantum yield (Fv / Fm), as a function of concentration, was verified in all treatments with exogenous cytokinins, except for the treatment with 5μM BAP. The most significant decrease in quantum yield was verified in plants treated with KIN. In the anatomical evaluation, the reduction of the stomatal functionality was verified, in response to the increased concentration of cytokinins. Exogenous cytokinins influence the physiology of the photosynthetic apparatus and the anatomy of A. blanchetiana seedlings during in vitro multiplication. KIN is not indicated for the multiplication of this species in vitro. The use of BAP at lower concentrations ensures a reduction of apical dominance and bud formation, with less degree of disturbance in the photosynthetic apparatus of the shoots